2013
DOI: 10.1186/ar4215
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress modulates macrophage-induced urokinase plasminogen activator expression in human chondrocytes

Abstract: IntroductionSynovial macrophages, which can release proinflammatory factors, are responsible for the upregulation of cartilage-breakdown proteases and play critical roles in cartilage degradation during the progression of osteoarthritis (OA). In addition, shear stress exerts multifunctional effects on chondrocytes by inducing the synthesis of catabolic or anabolic genes. However, the interplay of macrophages, chondrocytes, and shear stress during the regulation of cartilage function remains poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Previous in vivo studies have demonstrated that mechanical loading facilitates the strengthening of the bone and that flow‐induced shear force in the cartilage initiates a repair mechanism (Suh et al, ; Robling et al, ). Moreover, previous in vitro studies, both ours and others’, have indicated that low fluid shear stress (∼2–10 dyn/cm 2 ) may contribute to a chondroprotective effect on cartilage and that high shear stress (∼10–20 dyn/cm 2 ) may induce inflammation, cell death, and cartilage degradation (Yokota et al, ; Yeh et al, ; Wang et al, ; Zhu et al, ; Yeh et al, ; Guan et al, ). These studies have elucidated that the different intensities of shear forces may have a differential potential in regulating cellular signaling and function in chondrocytes and therefore control the cartilage homeostasis.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Previous in vivo studies have demonstrated that mechanical loading facilitates the strengthening of the bone and that flow‐induced shear force in the cartilage initiates a repair mechanism (Suh et al, ; Robling et al, ). Moreover, previous in vitro studies, both ours and others’, have indicated that low fluid shear stress (∼2–10 dyn/cm 2 ) may contribute to a chondroprotective effect on cartilage and that high shear stress (∼10–20 dyn/cm 2 ) may induce inflammation, cell death, and cartilage degradation (Yokota et al, ; Yeh et al, ; Wang et al, ; Zhu et al, ; Yeh et al, ; Guan et al, ). These studies have elucidated that the different intensities of shear forces may have a differential potential in regulating cellular signaling and function in chondrocytes and therefore control the cartilage homeostasis.…”
mentioning
confidence: 51%
“…Previous studies have demonstrated that fluid shear stress‐regulated cellular signaling and the function of chondrocytes are time‐, mode‐ and magnitude‐dependent. It has been indicated that high shear force promotes the catabolic destruction of cartilage, whereas the low shear stress effect on cartilage is chondroprotective (Yokota et al, ; Yeh et al, , ; Wang et al, ; Zhu et al, ; Guan et al, ). Our present results showed that the pre‐shear effect on cells with 2 dyn/cm 2 of shear stress attenuates the resistin effect on catabolic COX‐2 expression in human OA chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ined. ERK5 downregulation by siERK5 or XMD8-92 significantly inhibited 2 dyn/cm 2 shear force-increased KLF4 mRNA expression and p1901-Luc luciferase activity (Figure 5d) compared with siCL-or DMSO/shear force-treated cells.3.6 | PPARγ and KLF4 inhibit IL-1β-activated NF-κB in human primary and SW1353 chondrocytes under 2 dyn/cm 2 shear force stimulation Our previous studies have demonstrated the positive role of 2 dyn/cm 2 shear force in human primary chondrocytes(Su et al, 2017;Yeh et al, 2009Yeh et al, , 2013. Thus, we determined whether PPARγ-KLF4 play a downstream positive regulator of 2 dyn/cm 2 shear force in human chondrocytes.…”
mentioning
confidence: 81%